Low-odor starch-based biodegradable PBAT modified material and preparation method thereof
Modified starch is prepared by enzymatic removal of proteins and reacting with plasticizers, complexing agents and antioxidants, which solves the problem of burnt taste and color changes in the processing process of starch-based PBAT materials, and achieves materials with low odor, white and excellent heat sealing properties.
Patent Information
- Application Number
- CN202411756204.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art can easily lead to burnt smell and color changes in the processing process of starch-based PBAT materials, affecting the user experience and market value of the material.
Modified starch is prepared by enzymatically dissolving the starch with protease in aqueous solution, removing proteins, then alcoholylation and acidization with plasticizers and complexing agents, and finally transesterification reaction with antioxidants and catalysts.
It achieves low odor, white color and excellent heat sealing performance of starch-based materials, improving the user experience and market value of the materials.
Smart Images

Figure BDA0005166351650000051 
Figure BDA0005166351650000061 
Figure BDA0005166351650000062
Abstract
Description
Technical Field
[0001] The present invention relates to biodegradable materials, and in particular to a low-odor starch-based biodegradable PBAT modified material and a preparation method thereof. Background Art
[0002] Fully biodegradable plastics can be degraded by microorganisms in natural environments such as soil, and finally all become CO2 and organic matter. PBAT (polybutylene terephthalate-butylene adipate) is a biodegradable resin whose raw materials can all be directly derived from petrochemical raw materials. It not only has flexible aliphatic segments, but also rigid aromatic segments, which enables it to have good tensile properties while also having good molecular thermal stability, impact resistance and other mechanical properties, so it is widely used in disposable film bags and other fields; PLA (polylactic acid) is directly obtained by fermenting biomaterials such as starch to obtain lactide, and then ring-opening polymerization to obtain polylactic acid. PLA has a high modulus and is usually used to harden PBAT, thereby improving the stiffness of the material;
[0003] Starch is a green, renewable, fully biodegradable material with a wide range of sources and low prices. It is often filled into PBAT and / or PLA materials to reduce the cost of composite materials. However, starch is a highly polar crystalline substance with strong hydrogen bonds between and within molecules, poor thermoplasticity, difficulty in dispersion, and difficulty in filling high content into composite materials. It also exhibits crystal points. The traditional method is to add acid plasticizers and alcohol plasticizers to plasticize the native starch to prepare starch-based PBAT materials. Due to its good mechanical and degradation properties, starch-based PBAT materials are widely used in large supermarket bags and overseas vest bags. However, starch is subjected to heat and shear during processing, and the Maillard reaction occurs between reducing sugars and amino acids, proteins, and iron, resulting in a burnt smell in starch-based materials, which affects the use of the materials.
[0004] For example, CN113214616A discloses a low-odor biodegradable PLA alloy for food contact and its preparation method, which uses PBS, PLA, mineral powder, anti-hydrolysis agent, cross-linking agent, and flavor-modified porous silicon aluminum as raw materials, and is finally prepared by a twin-screw extruder. Due to the addition of flavor-modified porous silicon aluminum, the original smell of the plastic is masked, but at the same time, the odor of the flavor is introduced. CN117603402A adds acidic substances such as 1,4-succinic acid and maleic acid during the preparation of modified starch, and the compatibility of the composite modified starch with the degradable material resin is improved, which can increase the addition amount of the composite modified starch in the degradable plastic. CN 117510928 A prepares a high-toughness cellulose microgel / plasticized starch / PBAT film material, and a composite material with mechanical properties equivalent to PBAT can be obtained through high-toughness cellulose, acid and antioxidants.
[0005] However, the existing technology still has the following shortcomings: the degree of reducing the odor of starch materials by physical odor masking methods such as flavors is limited; small molecular acidic substances are added during the plasticization process of starch, which will cause the starch to coke during the shearing process, resulting in a strong odor and yellow color of the product; antioxidants are used in PBAT film systems without paying attention to their effects on long-term heat sealing performance. The above technical problems need to be solved urgently. Summary of the invention
[0006] In order to solve the above technical problems, one of the objects of the present invention is to provide a method for preparing modified starch. The modified starch obtained by the method is applied to degradable materials with low odor, white color and excellent heat sealing performance.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0008] A method for preparing modified starch, the method comprising the following steps:
[0009] S1: placing starch and protease in an aqueous solution for enzymatic hydrolysis, and obtaining protein-free starch after protein removal after separation;
[0010] S2: alcoholyzing and acidyzing the protein-free starch, the plasticizer and the complexing agent to obtain preformed starch;
[0011] S3: subjecting the prefabricated starch, the antioxidant and the catalyst to transesterification reaction, separating and drying, and obtaining the antioxidant modified starch.
[0012] The inventors have found that directly blending and modifying starch with PBAT will cause starch gelatinization and degradation due to shearing and heating in the screw, resulting in yellow material color and a strong burnt starch smell, which greatly affects the use experience and market value of the material. The present invention deproteinizes starch and modifies it with a complexing agent and an antioxidant. The modified starch obtained is applied to degradable materials with low odor, white color and excellent heat sealing performance.
[0013] In one embodiment of the present invention, the starch described in S1 is food-derived starch, preferably one or more of corn starch, cassava starch, wheat starch and potato starch; preferably, the mass ratio of starch to protease is 75-95:5-25, preferably 80-90:10-20.
[0014] In one embodiment of the present invention, the enzymatic hydrolysis temperature in S1 is 30-70°C, preferably 40-60°C, and the time is 0.3-1 h, preferably 0.5-0.8 h.
[0015] In one embodiment of the present invention, the mass fractions of the components in S2 are:
[0016] 70-90 parts of prefabricated starch, preferably 75-85 parts,
[0017] Complexing agent 1-3 parts, preferably 1.5-2.5 parts,
[0018] Plasticizer 10-25 parts, preferably 15-20 parts.
[0019] In one embodiment of the present invention, preferably, the plasticizer is selected from alcohol plasticizers, preferably one or more of methanol, ethanol, glycerol, and ethylene glycol, more preferably glycerol; preferably, the complexing agent is an amino acid-containing compound, preferably selected from ethylenediaminetetraacetic acid EDTA and / or aminotriacetic acid NTA.
[0020] In one embodiment of the present invention, the alcoholysis and acidolysis temperature in S2 is 50-90°C, preferably 60-80°C, and the time is 0.5-2.5h, preferably 1-2h.
[0021] In one embodiment of the present invention, alcoholysis and acidolysis are carried out under stirring in S2, preferably at a rotation speed of 2000-4000 rpm, more preferably 2500-3500 rpm; preferably for 0.3-1 h, more preferably 0.45-0.55 h.
[0022] In one embodiment of the present invention, the mass fractions of each component added in S3 are:
[0023] 70-90 parts of prefabricated starch, preferably 75-85 parts,
[0024] 1-5 parts of antioxidant, preferably 2.5-4.5 parts,
[0025] Catalyst 1-3 parts, preferably 1.5-2.5 parts.
[0026] In one embodiment of the present invention, preferably, the antioxidant is selected from one or more of amine antioxidants, hindered phenol antioxidants, thioester antioxidants, and phosphite antioxidants, preferably 1076 and / or 1010; preferably, the catalyst is one or more of alkaline earth metals, alkaline earth metal salts, and alkaline earth metal alkoxys, preferably one or more of KOH, NAOH, dibutyltin oxide, and potassium tert-butoxide.
[0027] In one embodiment of the present invention, the temperature of the starch modification reaction in S3 is 100-150° C., preferably 120-140° C., and the reaction time is 2-5 hours, preferably 3-4 hours.
[0028] In one embodiment of the present invention, the separation method in S3 is suction filtration or centrifugal separation, wherein the preferred conditions for centrifugal separation are a centrifugal speed of 6000-10000 rpm, preferably 7000-9000 rpm, and a centrifugal time of 0.3-1, preferably 0.4-0.5 h.
[0029] Another object of the present invention is to provide a modified starch.
[0030] A modified starch, wherein the modified starch is prepared by the above method, wherein the protein content of the modified starch is ≤0.1% by weight, and the molecular weight Mw is ≤1×10 5 .
[0031] Another object of the present invention is to provide a use of modified starch.
[0032] A use of modified starch, wherein the modified starch is prepared by the above method, or is the above starch, and the modified starch is used for preparing degradable materials or products thereof, preferably for preparing degradable film products.
[0033] Another object of the present invention is to provide a degradable material.
[0034] A degradable material, the material adopts the modified starch prepared by the above method, or adopts the above modified starch, and the material comprises the following components by weight:
[0035] PBAT resin 50-90 parts, preferably 65-85 parts,
[0036] PLA resin 0-10 parts, preferably 3-8 parts,
[0037] 10-35 parts of modified starch, preferably 15-30 parts,
[0038] Chain extender 0-0.5 parts, preferably 0.1-0.3 parts,
[0039] Lubricant 0-1 part, preferably 0.2-0.4 part.
[0040] In one embodiment of the present invention, preferably, the PBAT resin has a melt index of 3-8 g / 10 min at 190°C and 2.16 kg, and an acid value of 10-18; preferably, the PLA resin has a melt index of 3-10 g / 10 min at 190°C and 2.16 kg; preferably, the chain extender is an epoxy functional chain extender, preferably one or more of ADR4468, KL-E4370, BTCE-9013, and RELYON 4468; preferably, the lubricant is selected from amide and / or stearic acid, preferably one or more of erucamide, zinc stearate, and ethylene bis stearamide.
[0041] Another object of the present invention is to provide a method for preparing a degradable material.
[0042] A method for preparing a degradable material, wherein the material adopts the modified starch prepared by the above method, or adopts the above modified starch, or is the above degradable material, and the method comprises:
[0043] The modified starch, chain extender and lubricant are mixed and fed into a twin-screw extruder from the main feed, and PBAT and optionally PLA resin are added to the twin-screw extruder from the side feed, extruded, pelletized and dried after cooling to obtain a degradable material; preferably, the barrel temperature of the twin-screw extruder is not higher than 150°C, preferably 50-150°C; preferably, the screw speed of the twin-screw extruder is 200-400 rpm, preferably 250-350 rpm.
[0044] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0045] 1) Use protease to modify starch to prepare protein-free starch, avoid protein inactivation and reaction during processing, and reduce the odor of starch after processing;
[0046] 2) Use the low acidity of amino acid complexing agents to plasticize starch and avoid reaction with iron during processing, thereby reducing the odor of starch after processing;
[0047] 3) By reacting prefabricated starch with antioxidants, the thermal oxidative decomposition of the material during the extrusion process is reduced, and finally the antioxidant is connected with the starch to prevent subsequent film product precipitation and heat sealing failure. This invention can comprehensively obtain a biodegradable material with low odor, white color and excellent heat sealing performance. DETAILED DESCRIPTION
[0048] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0049] The sources of the main raw materials in the embodiments of the present invention are shown in Table 1:
[0050] Table 1
[0051]
[0052]
[0053] In Table 1, MFR represents the melt index of the polymer at 190°C and 2.16 kg, in g / 10 min. Unless otherwise specified, other raw materials and reagents can be purchased from commercial sources.
[0054] In each embodiment of the present invention, the main performance test methods of the degradable materials are shown in Table 2:
[0055] Table 2
[0056]
[0057] In addition, the test method for odor level is as follows:
[0058] Cut the film sample into 5cm*10cm size, take 10 sheets and put them into a 1L glass bottle, place them in a dark environment of constant temperature and humidity room for 24 hours, and test 3 groups of samples by 5 people to get the average value. Among them, the odor level 1 means basically slight odor, 2 means moderate non-irritating odor, 3 means irritating odor, and 4 means severe irritating odor.
[0059] The equipment used in the present invention mainly includes:
[0060] Twin-screw extruder, Coperion, model ZSK 26Mc 18, aspect ratio 40, screw diameter 26 cm;
[0061] Film blowing machine, Zhangjiagang Lianjiang Machinery Co., Ltd., model SCM 25, aspect ratio 30, screw diameter 25 cm;
[0062] German Gottfert melt indexer, test conditions are 190℃, 2.16kg;
[0063] German ZWICK universal material testing machine, tensile test condition is 500mm / min, right angle tear test condition is 200mm / min;
[0064] Jinan Labthink FDI-01 dart impact tester;
[0065] Humidity and heat aging chamber Espec Environmental Instruments (Shanghai) Co., Ltd.
[0066] Thermo Fisher infrared spectrometer IS10;
[0067] Agilent gel permeation chromatograph;
[0068] Thermo Fisher Dumas protein analyzer.
[0069] The following examples 1-3 are used to prepare modified starch AC:
[0070] Example 1
[0071] A method for preparing modified starch comprises the following steps:
[0072] 1) Weigh 80 g corn starch and 100 g deionized water to prepare a starch suspension solution; place 5 g protease in the solution, heat a water bath to 30° C. and stir for 60 min to fully mix, filter and dry at 80° C. for 4 h to obtain preformed starch 1 from which protein has been removed;
[0073] 2) 70 g of preformed starch 1, 1 g of EDTA and 10 g of glycerol were placed in a stirring agent, heated to 50° C. and stirred for 2.5 h to allow the preformed starch to undergo sufficient acid hydrolysis and alcoholysis to obtain preformed starch 2;
[0074] 3) 70 g of preformed starch 2, 1 g of 1010 and 1 g of KOH were added to methanol and mixed, stirred at 600 rpm for 4 min, then placed in an oil bath and heated and stirred, reacted at 90° C. for 5 h, cooled, filtered and separated to obtain modified starch A with a protein content of 0.05% and a Mw of 83566.
[0075] In infrared analysis, 1600cm -1 and 1449cm -1 The skeletal vibration of the benzene ring is at 3700-3100cm -1 The broad peak at 1732 cm corresponds to the stretching vibration peak of the -OH group. -1 The C=O stretching vibration peak shifted to 1744 cm -1 , indicating that antioxidant-modified low-protein modified starch was successfully synthesized.
[0076] Example 2
[0077] A method for preparing modified starch comprises the following steps:
[0078] 1) Weigh 85 g of cassava starch and 15 g of deionized water to prepare a starch suspension solution; place 10 g of protease in the solution, heat a water bath to 35° C. and stir for 48 min, mix thoroughly, filter and dry to obtain preformed starch 1 from which protein has been removed;
[0079] 2) 75 g of prefabricated starch 1, 1.5 g of NTA and 15 g of ethylene glycol were placed in a stirring agent, heated to 60° C. and stirred for 2 h to allow sufficient acid hydrolysis and alcoholysis to obtain prefabricated starch 2;
[0080] 3) 75 g of prefabricated starch 2, 2.5 g of 1010 and 1.5 g of NaOH were added to methanol and mixed, stirred at 600 rpm for 4 min, then placed in an oil bath and heated and stirred, reacted at 100° C. for 4 h, cooled, filtered and separated to obtain modified starch B with a protein content of 0.05% and a Mw of 87410.
[0081] Example 3
[0082] 1) Weigh 95 g of wheat starch and 15 g of deionized water to prepare a starch suspension solution; place 15 g of protease in the solution, heat a water bath to 45° C. and stir for 30 min, mix thoroughly, filter and dry to obtain preformed starch 1 from which protein has been removed;
[0083] 2) 85 g of prefabricated starch 1, 2.5 g of NTA and 20 g of sorbitol were placed in a stirring agent, heated to 80° C. and stirred for 60 min to allow sufficient acid hydrolysis and alcoholysis to obtain prefabricated starch 2;
[0084] 3) 85 g of prefabricated starch 2, 4.5 g of 1076 and 2.5 g of dibutyltin oxide were added to a 95% ethanol solution, mixed, stirred at 600 rpm for 4 min, heated in an oil bath and stirred, reacted at 120° C. for 3 h, cooled, filtered and separated to obtain modified starch C with a protein content of 0.045% and a Mw of 86541.
[0085] Example 4
[0086] A method for preparing modified starch comprises the following steps:
[0087] 1) Weigh 100 g of potato starch and 15 g of deionized water to prepare a starch suspension solution; place 20 g of protease in the solution, heat a water bath to 50° C., stir for 18 min, mix thoroughly, filter and dry to obtain a preformed starch 1 from which protein has been removed;
[0088] 2) 90 g of prefabricated starch 1, 3 g of NTA and 25 g of polyglycerol were placed in a stirring agent, heated to 90° C. and stirred for 30 min to allow sufficient acid hydrolysis and alcoholysis to obtain prefabricated starch 2;
[0089] 3) 90 g of prefabricated starch 2, 5 g of 1076 and 3 g of potassium tert-butoxide were added to 95% ethanol, mixed, stirred at 600 rpm for 4 min, then placed in an oil bath for heating and stirring, reacted at 130° C. for 2 h, cooled, filtered and separated to obtain modified starch D with a protein content of 0.04% and a Mw of 85433.
[0090] Comparative Example 1
[0091] Modified starch E was prepared by the same method as in Example 2, except that no protease was added in step 1). The modified starch E had a protein content of 0.45% and a Mw of 87410.
[0092] Comparative Example 2
[0093] Modified starch F was prepared by the same method as in Example 2, except that no complexing agent NTA was added in step 2. The modified starch F had a protein content of 0.05% and a Mw of 87410.
[0094] Comparative Example 3
[0095] Modified starch G was prepared in the same manner as in Example 2, except that no antioxidant was added in step 3). The modified starch G had a protein content of 0.05% and a Mw of 87410.
[0096] Comparative Example 4
[0097] Compared with Example 2, modified starch was prepared in the same manner as Example 2, except that physical blending was performed in step 3), and the antioxidant had no reaction with the starch. 75 g of preformed starch 2, 2.5 g of 1010, and 1.5 g of NaOH were added to methanol, mixed, stirred at 600 rpm for 4 min, and separated by suction filtration to obtain modified starch H. The protein content was 0.05%, and the Mw was 87410.
[0098] The following examples 5-8 are used to prepare degradable materials:
[0099] Example 5
[0100] A degradable material, based on a total weight of 10 kg, comprises the following components:
[0101] T16 50 copies,
[0102] Modified starch A 35 parts,
[0103] ADR4468 0.1 part,
[0104] 0.1 part of ethylene bis stearamide;
[0105] The method for preparing the above-mentioned degradable material comprises the following steps:
[0106] Modified starch A, chain extender ADR4468, and ethylene bis stearamide were mixed in a low-speed mixer for 2 minutes, added to the main feed port of the twin-screw extruder, and T16 was mixed in a low-speed mixer for 2 minutes, added to the side feed port of the twin-screw extruder for melt extrusion. The extrusion conditions are: screw speed 200rpm, screw temperature from the feed port to the die section is set to: 50℃, 50℃, 50℃, 50℃, 50℃, 50℃, 110℃, 130℃, 110℃, 110℃, 110℃, 100℃. The extruded material was cooled and pelletized in the extruder water tank, and placed in an 80℃ oven for 4 hours for drying to obtain degradable material A.
[0107] Example 6
[0108] A degradable material, based on a total weight of 10 kg, comprises the following components:
[0109] C1200 65 copies,
[0110] LX575 5 copies,
[0111] Modified starch B 30 parts,
[0112] ADR4468 0.3 parts,
[0113] 0.2 parts of zinc stearate;
[0114] The method for preparing the above-mentioned degradable material comprises the following steps:
[0115] Modified starch B, chain extender ADR4468, and zinc stearate were mixed in a low-speed mixer for 2 minutes, added to the main feed port of the twin-screw extruder, MGJH901S and LX575 were mixed in a low-speed mixer for 2 minutes, added to the side feed port of the twin-screw extruder, and melt extruded. The extrusion conditions are: screw speed 200rpm, screw temperature from the feed port to the die section is set to: 60℃, 60℃, 60℃, 60℃, 60℃, 60℃, 120℃, 140℃, 120℃, 120℃, 120℃, 100℃. The extruded material was cooled and pelletized in the extruder water tank, placed in an 80℃ oven for 4 hours for drying, and degradable material B was obtained.
[0116] Example 7
[0117] A degradable material, based on a total weight of 10 kg, comprises the following components:
[0118]
[0119] The method for preparing the above-mentioned degradable material comprises the following steps:
[0120] Modified starch C, chain extender KL-E4370, antioxidant 1010, antioxidant 168, and erucic acid amide were mixed in a low-speed mixer for 2 minutes and added to the main feed port of the twin-screw extruder. DT-10A and LX175 were mixed in a low-speed mixer for 2 minutes and added to the side feed port of the twin-screw extruder for melt extrusion. The extrusion conditions are: screw speed 200rpm, screw temperature from the feed port to the die section is set to: 70℃, 70℃, 70℃, 70℃, 70℃, 70℃, 130℃, 140℃, 130℃, 130℃, 130℃, 100℃. The extruded material was cooled and pelletized in the extruder water tank, and placed in an 80℃ oven for 4 hours for drying to obtain degradable material C.
[0121] Example 8
[0122] A degradable material, based on a total weight of 10 kg, comprises the following components:
[0123]
[0124] The method for preparing the above-mentioned degradable material comprises the following steps:
[0125] Modified starch A, chain extender BTCE-9013, and erucic acid amide were mixed in a low-speed mixer for 2 minutes, and added to the main feed port of the twin-screw extruder. T16 and LX175 were mixed in a low-speed mixer for 2 minutes, and added to the side feed port of the twin-screw extruder for melt extrusion. The extrusion conditions are: screw speed 200rpm, screw temperature from the feed port to the die section is set to: 70℃, 70℃, 70℃, 70℃, 70℃, 70℃, 130℃, 140℃, 130℃, 130℃, 130℃, 100℃. The extruded material was cooled and pelletized in the extruder water tank, and placed in an 80℃ oven for 4 hours for drying to obtain degradable material D.
[0126] Comparative Example 5
[0127] Degradable material E was prepared in substantially the same manner as in Example 6, except that modified starch B was replaced by modified starch E.
[0128] Comparative Example 6
[0129] Degradable material F was prepared in substantially the same manner as in Example 6, except that modified starch B was replaced by modified starch F.
[0130] Comparative Example 7
[0131] The degradable material G was prepared in substantially the same manner as in Example 6, except that the modified starch B was replaced by modified starch G.
[0132] Comparative Example 8
[0133] The degradable material H was prepared in substantially the same manner as in Example 6, except that the modified starch B was replaced by modified starch H.
[0134] The degradable materials prepared in Examples 5-8 and Comparative Examples 5-8 were extruded and granulated, respectively, and marked as particles AD and EI, and blown films were made to obtain films with a thickness of 25 microns, which were marked as films AD and EI. The crystal point conditions of each film were visually judged (the number of crystal points with a crystal point size greater than 0.2 mm under a sample size of 150 mm*150 mm), and the mechanical properties of the film were tested by a tensile machine. The test results are shown in Table 3.
[0135] Table 3. Performance test results
[0136]
[0137] It can be seen from the data in Table 3 that the overall performance of the embodiments is better than that of the comparative examples. It can be seen that the degradable material prepared by the modified starch of the present invention uses protease to remove protein from starch, uses a weakly acidic chelating agent to avoid degradation of starch by strong acid and reaction of starch with iron, plasticizes the starch, has few film crystal points, and synergizes with antioxidants to reduce shear degradation during starch processing, has good initial mechanical properties, color and smell, and solves the problem of low heat sealing strength caused by subsequent precipitation of antioxidants, thereby improving the overall heat sealing cycle of the material.
[0138] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for preparing modified starch, characterized in that: The preparation method comprises the following steps: S1: placing starch and protease in an aqueous solution for enzymatic hydrolysis, and obtaining protein-free starch after protein removal after separation; S2: alcoholyzing and acidyzing the protein-free starch, the plasticizer and the complexing agent to obtain preformed starch; S3: subjecting the prefabricated starch, the antioxidant and the catalyst to transesterification reaction, separating and drying, and obtaining the antioxidant modified starch.
2. The preparation method according to claim 1, characterized in that: S1 The starch is food-derived starch, preferably one or more selected from corn starch, tapioca starch, wheat starch and potato starch; Preferably, the mass ratio of starch to protease is 75-95:5-25, preferably 80-90:10-20; And / or, the enzymatic hydrolysis temperature in S1 is 30-70°C, preferably 40-60°C, and the time is 0.3-1h, preferably 0.5-0.8h.
3. The preparation method according to claim 1, characterized in that: The mass fractions of each component in S2 are: 70-90 parts of prefabricated starch, preferably 75-85 parts, Complexing agent 1-3 parts, preferably 1.5-2.5 parts, 10-25 parts of plasticizer, preferably 15-20 parts; Preferably, the plasticizer is selected from alcohol plasticizers, preferably one or more of methanol, ethanol, glycerol, and ethylene glycol, more preferably glycerol; Preferably, the complexing agent is an amino acid-containing compound, preferably selected from ethylenediaminetetraacetic acid EDTA and / or aminotriacetic acid NTA; and / or, the alcoholysis and acidolysis temperature in S2 is 50-90°C, preferably 60-80°C, and the time is 0.5-2.5h, preferably 1-2h; And / or, alcoholysis and acidolysis are carried out under stirring conditions in S2, preferably at a rotation speed of 2000-4000 rpm, more preferably 2500-3500 rpm; preferably for 0.3-1 h, more preferably 0.45-0.55 h.
4. The preparation method according to claim 1, characterized in that: The mass fractions of each component added in S3 are: 70-90 parts of prefabricated starch, preferably 75-85 parts, 1-5 parts of antioxidant, preferably 2.5-4.5 parts, 1-3 parts of catalyst, preferably 1.5-2.5 parts; Preferably, the antioxidant is selected from one or more of amine antioxidants, hindered phenol antioxidants, thioester antioxidants, and phosphite antioxidants, preferably 1076 and / or 1010; Preferably, the catalyst is one or more of alkaline earth metals, alkaline earth metal salts, alkaline earth metal alkoxides, preferably one or more of KOH, NAOH, dibutyltin oxide and potassium tert-butoxide; And / or, the temperature of the starch modification reaction in S3 is 100-150° C., preferably 120-140° C.; the reaction time is 2-5 hours, preferably 3-4 hours; And / or, the separation method in S3 adopts suction filtration or centrifugal separation, wherein the preferred conditions for centrifugal separation are: centrifugal speed 6000-10000 rpm, preferably 7000-9000 rpm, centrifugal time 0.3-1, preferably 0.4-0.5h.
5. A modified starch, wherein the modified starch is prepared by the method according to any one of claims 1 to 4, characterized in that: The modified starch has a protein content of ≤0.1% and a molecular weight of ≤1×10 5 .
6. Use of a modified starch, wherein the modified starch is prepared by the method according to any one of claims 1 to 4, or is the starch according to claim 5, and the modified starch is used to prepare a degradable material or a product thereof, preferably to prepare a degradable film product.
7. A degradable material, wherein the material is made of the modified starch obtained by the method according to any one of claims 1 to 4, or the modified starch according to claim 5, characterized in that: The material comprises the following components by weight: PBAT resin 50-90 parts, preferably 65-85 parts, PLA resin 0-10 parts, preferably 3-8 parts, 10-35 parts of modified starch, preferably 15-30 parts, Chain extender 0-0.5 parts, preferably 0.1-0.3 parts, Lubricant 0-1 part, preferably 0.2-0.4 part; Preferably, the PBAT resin has a melt index of 3-8 g / 10 min at 190° C. and 2.16 kg, and an acid value of 10-18; Preferably, the PLA resin has a melt index of 3-10 g / 10 min at 190° C. and 2.16 kg; Preferably, the chain extender is an epoxy functionalized chain extender, preferably one or more of ADR4468, KL-E4370, BTCE-9013, and RELYON4468; Preferably, the lubricant is selected from amides and / or stearic acid, preferably one or more of erucic acid amide, zinc stearate and ethylene bis stearamide.
8. A method for preparing a degradable material, wherein the material is the modified starch prepared by the method according to any one of claims 1 to 4, or the modified starch according to claim 5, or the degradable material according to claim 7, characterized in that: The method is: The modified starch, chain extender and lubricant are mixed and fed into a twin-screw extruder from the main feed, and PBAT and optionally PLA resin are fed into the twin-screw extruder from the side feed, extruded, pelletized and dried after cooling to obtain a degradable material; Preferably, the barrel temperature of the twin-screw extruder is not higher than 150°C, preferably 50-150°C; Preferably, the screw speed of the twin-screw extruder is 200-400 rpm, preferably 250-350 rpm.
Citation Information
Patent Citations
Preparation method of high-toughness cellulose microgel / plasticized starch / PBAT (poly (butyleneadipate-co-terephthalate)) membrane material
CN117510928A
Composite modified starch for biodegradable plastic and preparation method thereof
CN117603402A